Therapeutic Plasma Exchange Application in Children Requires Individual Decision - Atay, Gürkan; Demirkol, Demet (Journal of Pediatric Intensive Care, 2020)
Therapeutic plasma exchange (TPE) is a treatment administered with the aim of removing a pathogenic material or compound causing morbidity in a variety of neurologic, hematologic, renal, and autoimmune diseases. In this study, we aimed to assess the indications, efficacy, reliability, complications, and treatment response of pediatric patients for TPE. This retrospective study analyzed data from 39 patients aged from 0 to 18 years who underwent a total of 172 TPE sessions from January 2015 to April 2018 in a tertiary pediatric intensive care unit. Indications for TPE were, in order of frequency, macrophage activation syndrome (28.2%, n = 11), renal transplantation rejection (15.4%, n = 6), liver failure (15.4%, n = 6), Guillain–Barre's syndrome (15%, n = 6), hemolytic uremic syndrome (7.7%, n = 3), acute demyelinating disease (7.7%, n = 3), septic shock (5.1%, n = 2), and intoxication (5.1%, n = 2). No patient had any adverse event related to the TPE during the procedure. The TPE session was ended prematurely in one patient due to insufficient vascular access and lack of blood flow (2.6%). In the long term, thrombosis due to the indwelling central catheter occurred (5.1%, n = 2). TPE appears to be an effective first-stage or supplementary treatment in a variety of diseases, may be safely used in pediatric patients, and there are significant findings that its area of use will increase. In experienced hands and when assessed carefully, it appears that the rate of adverse reactions and vascular access problems may be low enough to be negligible.
Keywords: therapeutic plasma exchange; pediatric; indications